Healthcare services: Halal pharmaceutical in Malaysia, issues and challenges - Ramli, Noriah; Amin, Naemah; Zawawi, Majdah; Abdul Aziz, Norazlina (The Malaysian Consumer Family Economics Association, 2017)
Halal industry is often associated with the many issues and is a global multibillion dollar business. More recently however Malaysia has taken the lead in an endeavour to label pharmaceutical products with the halal certification. As a new industry, numerous challenges exist. One of which is the need for an effective legal framework that governs the halal pharmaceutical products. This article examines the existing legal framework for the halal pharmaceutical products through the doctrinal studies and interview with the stakeholders. The findings reveal several challenges in implementing the law with regard to the halal pharmaceutical products.